Human rights and human well-being - Talbott, W. J. (New York ; Oxford : Oxford University Press, 2010)
Explaining the development of human rights as a process of moral improvement in ground level moral and legal practices, the author considers the process by which moral and legal practices are improved. There is focus on moral improvement and how to apply the model of moral improvement to improvements in the law.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Human rights -- Philosophy; Human rights -- Moral and ethical aspects